Taking America back the conservative movement and the far right - Walsh, David Austin (Yale University Press, 2024)
"A provocative look at the relationship between the far right and the American conservative movement from the 1930s to the end of the Cold War."
Keywords: Geschichte 1930-1989; Konservativismus; Rechtsradikalismus; USA